Analisis pengaruh profil sudu dan jumlah sudu terhadap unjuk kerja turbin angin poros horizontal pada daerah kecepatan angin rendah - I.K. Wiratama; I.D.K. Okariawan; I.G.N.K Yudhyadi; I.M. Mara; A. Juliansah (Universitas Mataram, 2019)
Wind Energy is one of the renewable energy sources, therefore utilizing wind energy during this time is very wide. Indonesia has enormous wind energy potential with wind speeds between 2 m/s to6 m/s, and especially in the Nusa Tenggara region can reach wind speeds> 5 m/s. To enable rising solar energy (10 kW) and (10-100 kW).This research was conducted to obtain the performance characteristics of horizontal axle wind turbine with variation of blade profile and number of different blades in each test. Wind source is obtained with the help of wind power 7 m/s wind speed. The shape of the blade that is used there are four variations of the big taper, half thin small, half tapered and small taper. The test is also carried out with variations of the blade amounts of 3, 4, 5 and 6.The results are shown in the graph of the number of blades against the rotation of the rotor, the amount of the blade to the rotor rotation after braking, the amount of the blade to the rotor power, the amount of the blade to the torque, the amount of the blade to the cpR and the amount of the blade against the Speed Ratio Tip (TSR). The maximum rotor rotation speed is generated on the form of a large tapered blade with an amount of 3 blades of 865.76 rpm. The maximum rotor and torque power is generated on the form of a large tapered blade with an amount of 4 blades which is 182.01 Watt and 3.25 Nm. Maximum CpR is produced on the form of a large tapered blade with an amount of 4 blades which is 0.48 as a result of TSR of 8.69. So of all variations done, the best result results on a large tapered blade with 4 blades